An analytical technique for solving quadratic nonlinear oscillator. Issue 3 (4th October 2017) - Molla, Md. Helal Uddin; Razzak, Md. Abdur; Alam, M.S.
Abstract : Purpose: The purpose of this paper is to present an analytical technique, based on the He's energy balance method (an improved version recently presented by Khan et al. ), to obtain the approximate solution of quadratic nonlinear oscillator (QNO). Design/methodology/approach: This oscillator (QNO) is used as a mathematical model of the human eardrum oscillation. Findings: It has been shown that the results by the present technique are very close to the numerical solution. Originality/value: The results obtained in this paper are compared with those obtained by Hu (harmonic balance method) and Khan et al. The result shows that the method is more accurate and effective than harmonic balance as well as improved energy balance methods.